Implementation of TRIPS flexibilities and injunctions: A case study of India - Shirin Syed (South Centre, 2024)
The proponents of intellectual property (IP) have increasingly utilized injunctions with indiscriminate propensity as a strategic tool for IP enforcement, resulting in adverse socio-economic implications, including the enjoyment of human rights. This trend has eclipsed the flexibilities provided in the Doha Declaration on the TRIPS Agreement and Public Health. Although a substantial volume of the literature focuses on the flexibilities of compulsory license or scope of patentability, little attention has been given to the flexibilities related to IP enforcement. Discussing the implications of IP enforcement on public interest, the paper examines the gaps in the articulation of flexibilities of intellectual property rights (IPRs) enforcement, with special reference to injunctions in India. It examines how far the courts consider the implications on the enjoyment of fundamental rights while granting injunctions on patents. This paper argues that the Indian courts have deviated from the cautious approach provisioned under the TRIPS flexibilities that allows the courts to consider the public interest aspect and human rights implications while granting injunctions in patent litigation. Moreover, it asserts that the courts should exercise prudence in granting injunctive relief in cases involving patent infringement, and take into account the potential impact of such relief on the exercise of human rights. This suggests a need for a careful examination of the potential implications of injunctive remedies in such cases.
Keywords: 300; Intellectual property rights; patent law; TRIPS; law enforcement; India; Immaterialgüterrechte; Patentrecht; TRIPS; Rechtsdurchsetzung; Indien